2023
DOI: 10.1186/s12912-023-01334-5
|View full text |Cite
|
Sign up to set email alerts
|

The experience of nurses to reduce implicit rationing of nursing care: a phenomenological study

Abstract: Background Implicit rationing of nursing care can adversely affect patient safety and the quality of care, and increase nurses’ burnout and turnover tendency. Implicit rationing care occurs at the nurse-to-patient level (micro-level), and nurses are direct participants. Therefore, the strategies based on experience of nurses to reduce implicit rationing care have more reference value and promotion significance. The aim of the study is to explore the experience of nurses to reduce implicit ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Furthermore, nurses are the mainstay of clinical care, and their attitudes are key factors in shaping the overall quality of care. A positive, optimistic, and confident attitude toward life can lead to quality nursing care and inspire nurses to commit to their work [ 44 ]. Although the majority of the participants in this study indicated that they maintained a focused and devoted attitude towards their nursing work, some participants mentioned potentially negative attitudes owing to work pressure or for other reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, nurses are the mainstay of clinical care, and their attitudes are key factors in shaping the overall quality of care. A positive, optimistic, and confident attitude toward life can lead to quality nursing care and inspire nurses to commit to their work [ 44 ]. Although the majority of the participants in this study indicated that they maintained a focused and devoted attitude towards their nursing work, some participants mentioned potentially negative attitudes owing to work pressure or for other reasons.…”
Section: Discussionmentioning
confidence: 99%